A long winter for the Red Queen: rethinking the evolution of seasonal migration. (4th November 2018) - Winger, Benjamin M.; Auteri, Giorgia G.; Pegan, Teresa M.; Weeks, Brian C.
Abstract: This paper advances an hypothesis that the primary adaptive driver of seasonal migration is maintenance of site fidelity to familiar breeding locations. We argue that seasonal migration is therefore principally an adaptation for geographic persistence when confronted with seasonality – analogous to hibernation, freeze tolerance, or other organismal adaptations to cyclically fluctuating environments. These ideas stand in contrast to traditional views that bird migration evolved as an adaptive dispersal strategy for exploiting new breeding areas and avoiding competitors. Our synthesis is supported by a large body of research on avian breeding biology that demonstrates the reproductive benefits of breeding‐site fidelity. Conceptualizing migration as an adaptation for persistence places new emphasis on understanding the evolutionary trade‐offs between migratory behaviour and other adaptations to fluctuating environments both within and across species. Seasonality‐induced departures from breeding areas, coupled with the reproductive benefits of maintaining breeding‐site fidelity, also provide a mechanism for explaining the evolution of migration that is agnostic to the geographic origin of migratory lineages (i.e. temperate or tropical). Thus, our framework reconciles much of the conflict in previous research on the historical biogeography of migratory species. Although migratory behaviour and geographic range change fluidly and rapidly in many populations, we argue that the loss of plasticity for migration via canalization is an overlooked aspect of the evolutionary dynamics of migration and helps explain the idiosyncratic distributions and migratory routes of long‐distance migrants. Our synthesis, which revolves around the insight that migratory organisms travel long distances simply to stay in the same place, provides a necessary evolutionary context for understanding historical biogeographic patterns in migratory lineages as well as the ecological dynamics of migratory connectivity between breeding and non‐breeding locations.